Molecular quantification of gbpA1 gene expression in Vibrio cholerae exposed to Hunteria umbellata methanol leaf extract - Titilola F. SALISU; Muinah A. FOWORA; Tajudeen O. YAHAYA; Tawakalt A. FAGBAYI; Oyindamola J. SAMSON; Halima AUDU-OHIDA (Notulae Scientia Biologicae)
Leaves are the most common parts of Hunteria umbellata used to treat cholera infections in traditional medicine. However, inappropriate doses are often abused. Despite continuous colonization of small intestine epithelium by Vibrio cholerae (VC), there is a paucity of literature in in vitro molecular toxicology of graded doses of H. umbellata leaf extract. Particularly, targeting the effect on gene expression of N-acetyl glucosamine-binding protein A (GbpA), which is critical to thwart indiscriminate consumption during cholera treatment. This study evaluated in vitro molecular toxicological activities of V. cholerae exposed to eight varying concentrations (500 to 3.90625 μgμL-1) of methanol H. umbellata leaf extract. The broth microdilution method was employed for bacterial assay, and two-step reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) was harnessed to quantify expression of the GbpA I gene. The hybrid gas chromatograph–mass spectrometer (GC–MS) technique was used to identify chemical components in H. umbellata. Results disclosed significant (p < 0.05) dose-response mode toxicity in the bactericidal property of all tested concentrations of H. umbellata leaf extract compared to controls. Quantified expression of GbpA I in V. cholerae was most significantly elevated (p < 0.05) at 500 μgμL-1 and least at 125 μgμL-1 of H. umbellata extract when compared with control. Eight phytochemicals and ten analytical grade compounds were identified, predominantly constituting fatty acids. Conspicuously, the research highlighted the potential menace of amplified V. cholerae infection at higher doses of H. umbellata leaf extract, ascribed to the expression of the virulence factor GbpA I gene, that initiates colonization of intestines and persistent reinfection of cholera. Thus, the general populace should be alerted of dangers involved in excessive drinking of infused H. umbellata leaf to treat diarrhea, as it could lead to augmented expression of the gene responsible for more severe cholera disease.